2008
DOI: 10.1021/jf0729513
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Fumonisin B1 in Corn Grits by Single-Screw Extrusion

Abstract: This study was designed to determine the efficacy of extrusion in reducing fumonisin B1 in corn flaking grits in the presence and absence of glucose. In addition, degradation products of fumonisin B1 during extrusion were identified and quantitated with a mass balance approach. Uncontaminated clean corn grits, grits spiked with 30 microg/g fumonisin B1, and grits fermented with Fusarium verticillioides M-2552 (40-50 microg/g fumonisin B1) were extruded in the presence and absence of glucose (10%, w/w) using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 27 publications
1
32
0
2
Order By: Relevance
“…While FB 1 is very heat stable and survives conventional heat processes, such as baking and frying (Jackson and others 1997), previous studies suggest that extrusion may reduce the toxin in finished food products (Katta and others 1999; Pineiro and others 1999). Bullerman and others (2008) studied the effect of single‐screw extrusion on the reduction of FB 1 in corn grits in the presence and absence of glucose. The results indicated that the extrusion process reduced the amount of FB 1 by 21% to 37% in the absence of sugar, while the addition of glucose further decreased the toxin by 77% to 87%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While FB 1 is very heat stable and survives conventional heat processes, such as baking and frying (Jackson and others 1997), previous studies suggest that extrusion may reduce the toxin in finished food products (Katta and others 1999; Pineiro and others 1999). Bullerman and others (2008) studied the effect of single‐screw extrusion on the reduction of FB 1 in corn grits in the presence and absence of glucose. The results indicated that the extrusion process reduced the amount of FB 1 by 21% to 37% in the absence of sugar, while the addition of glucose further decreased the toxin by 77% to 87%.…”
Section: Introductionmentioning
confidence: 99%
“…During thermal processes, such as extrusion, fumonisins are believed to react with reducing sugars to form sugar adducts such as NDF‐FB 1 , NCM‐FB 1 , and other N ‐substituted FB 1 compounds that can be detected by LC‐mass spectrometry (LC‐MS) (Murphy and others 1996; Lu and others 2002; Poling and others 2002; Bullerman and others 2008). Thermal processing may also result in binding of FB 1 to proteins and starches in the food matrix to cause reduction in recovery (Kim and others 2003; Seefelder and others 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The products of such reactions include N-(deoxy-D-fructos-1-yl)-fumonisin B 1 (NDF-FB 1 ) produced by the Amadori rearrangement of the Schiff's base while the FB 1 primary amine reacts with a D-glucose aldehyde group and N-carboxymethyl-fumonisin B 1 (NCM-FB 1 ) produced from NDF-FB 1 (Bullerman, Bianchini, Jackson, Jablonski, & Ryu, 2008;Poling, Plattner, & Weisleder, 2002). Other forms fumonisins (which include hidden fumonisins) also occur naturally.…”
Section: Introductionmentioning
confidence: 96%
“…Extrusion cooking improves the quality by modifying the texture or increasing the digestibility of the processed products. In addition, it can affect the levels of mycotoxins in final products (Bullerman et al 2008;Castells, Marin, Sanchis, & Ramos, 2005;Jackson, Voss, & Ryu, 2012;Wu, Lohrey, Cramer, Yuan, & Humpf, 2011). For instance, approximately 95% of Deoxynivalenol (DON) was removed by extruding maize flour at 150e180 C (Cazzaniga, Basilico, Gonzaalez, Torres, & de Greef, 2001).…”
Section: Introductionmentioning
confidence: 99%